Development of a Class XI Citizenship Education Learning Model Based on Blended Learning Flipped Classroom at Tunas Bangsa Vocational School, Depok - Umri Sofyan Sori; Nurdin Ibrahim; Rudi Hartono (IJOEM: Indonesian Journal of E-learning and Multimedia, 2024)
The aim of this research is to develop and test the feasibility and effectiveness of developing a Class XI Civics Education Learning Model Based on Blended Learning-Flipped Classroom at Tunas Bangsa Vocational School, Depok. This research uses the development of the Borg and Gall model which is integrated with the Rowntree model with 9 steps from the Bord and Gall model, and 3 steps from the Rowntree model. The results of the feasibility test carried out by material experts were 81%, processional design experts 94%, and media experts 88%, teacher users 87% and student users 83%. Overall, the results were in the "very feasible" category. These results indicate that the use of electronic modules is suitable for improving the learning outcomes of students in class XI citizenship education subjects at Tunas Bangsa Vocational School, Depok. The results of the effectiveness test were shown by comparing the post test results of the experimental class and the post test results of the control class with a total of 10 students as respondents. Statistical analysis uses an independent sample t test with a value of tcount > ttable or 5.080 > 2.101 at a significance level of 5% and df = 18, so Ho is rejected and Ha is accepted. Based on these findings, it can be concluded that the use of electronic modules as a learning medium for class XI citizenship education based on blended learning flipped classrooms is effectively used to improve student learning outcomes.